ANALISIS PERBEDAAN HARGA SAHAM SEBELUM DAN SESUDAH WABAH SARS (STUDI EMPIRIS PADA INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA) - Dewi Kusuma Wardani; Anita Primastiwi; Yulianus Celni Budiarto (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2022)
This study aims to determine the level of stock prices contained in the Indonesian capital market or commonly called the Indonesia Stock Exchange (IDX) during the SARS outbreak period in 2003. The method used in this study is a quantitative method. The study used a sample of all companies listed and active in trading on the Indonesia Stock Exchange. sample using purposive sampling method. Sampling of data is done by downloading the daily stock price data on the official website of the Indonesia Stock Exchange (IDX). The number of samples processed was 188 samples. The research data was then processed using the Statistical Package for the Social Sciences 20 (SPSS 20) application. The results of the paired sample t-test showed a t-count value of 329 with a significance level of 0.743 or above 5% significance, it can be stated that the hypothesis that there is a difference in stock prices before and after the SARS outbreak is rejected, meaning that there is no difference in stock prices before and after the SARS outbreak.